Glycosylated Hemoglobin as an Age-Specific Predictor and Risk Marker of Colorectal Adenomas in Non-Diabetic Adults - Yu, Xinyan; Chen, Chen; Song, Xiaoxiao; Guo, Yi; Tong, Yuling; Zhao, Yi; Song, Zhenya (Frontiers in Endocrinology, 2021)
Background Diabetes is a risk factor for colorectal neoplasms. The association between the level of glycosylated hemoglobin (HbA1c) and the risk of colorectal adenomas (CRAs) in non-diabetic adults needs to be investigated. Methods A cross-sectional study was performed on non-diabetic adults with normal HbA1c level who underwent colonoscopy between January 2010 and December 2016 during health check-ups in our hospital in China. The association between HbA1c level and CRAs was assessed by multivariable logistic regression models stratified by age group (<40, ≥40 and <50, and ≥50 years old). The age group-specified thresholds for HbA1c on elevated risk of CRAs were estimated using the piecewise logistic regression. Results Among the 2,764 subjects, 445 (16.1%) had CRA. The prevalence of CRA varied across the three age groups. A higher HbA1c level was found to be significantly associated with increased CRA risk in the 40–50 years group (odds ratio [OR]=1.70, 95% confidence interval [CI] 1.04–2.78, p=0.035) after adjusting for other related factors, while this association was borderline significant among the 50 years and older group (OR=1.57, 95% CI 0.97–2.54, p=0.067). Based on the piecewise logistic regression analysis results, the thresholds for HbA1c on elevated risk of CRA were 5.44% for the 40–50 years group and 4.81% for the 50 years and older group, respectively. Conclusions Higher levels of HbA1c, even within the normal range, were associated with elevated CRA risk among non-diabetic adults. The threshold effects of HbA1c on the risk of CRA varied across different age groups, and early screening colonoscopy might be needed for individuals in their 40s and with HbA1c levels ≥5.44%.